Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

For $0 \le x \le 1 , p\gt 1$, prove $1 \over2^{p-1}$ $\le x^p +(1-x)^p \le 1$.

share|cite|improve this question
up vote 4 down vote accepted

One way to prove the first inequality is to use the fact that $x\mapsto x^p$ is a convex function to observe that $$\frac{1}{2^p}= \left(\frac{x+(1-x)}{2}\right)^p\leq \frac{x^p+(1-x)^p}{2}.$$ I prefer this method because it seems more insightful.

However, you can also do the straightforward thing and differentiate $x^p+(1-x)^p$, which for $p>1$ gives $px^{p-1}-p(1-x)^{p-1}$. This is zero iff $x=1-x$, i.e. $x=1/2$. Thus the extrema of $x^p+(1-x)^p$ occur at $0,1/2,1$ and you can observe that the value of $x^p+(1-x)^p$ at these points is $1,1/2^{p-1}$ and $1$ respectively.

share|cite|improve this answer

From the answer here, we have for a real number $p \geq 1$ and complex numbers $\alpha, \beta$, \begin{equation} |\alpha + \beta|^p \leq 2^{p-1}(|\alpha|^p + |\beta|^p) \end{equation} In your case, take $\alpha = x \in [0,1]$ and $\beta = 1-x$ to obtain the lower bound on $x^p + (1-x)^p$. The upper bound is trivial since for $p>1$ and $x \in [0,1]$, we have $$x^p \leq x \,\, \text{ and } \,\, (1-x)^p \leq 1-x$$ Hence, we get $$x^p + (1-x)^p \leq x + 1-x = 1$$which gives us the upper bound.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.